GENIUS STATE OF MIND – DETERMINATION OR EFFECT? - Vlad Cristian DEAC (Studia Universitatis Babeș-Bolyai. Philosophia)
Genius State of Mind – Determination or Effect? Through this paper I put together philosophical aspects and also medical ones regarding Nietzsche’s mental disorders. The analyze is based on three different discussions on modeling or creative suffering, bipolar disorder and altered states of consciousness ‒ extended consciousness and will show us some interesting findings, one of them is that the bipolar disorder II that Nietzsche was suffering of, could be the trigger point for it’s genius state of mind. Also in the discussions chapter some questions regarding genius are raised.